STABILITY ANALYSIS OF THREE-DIMENSIONAL TRUSSES - GRECO, M. (2006)
THIS PAPER PRESENTS A NEW GEOMETRIC NONLINEAR FORMULATION FOR STABILITY ANALYSIS INVOLVING 3D TRUSSES. THE PROPOSED FORMULATION IS BASED ON THE FINITE ELEMENT METHOD (FEM) AND USES NODAL POSITIONS RATHER THAN NODAL DISPLACEMENTS TO DESCRIBE THE PROBLEM. THE STRAINS ARE COMPUTED DIRECTLY FROM THE PROPOSED POSITION CONCEPT, USING A CARTESIAN CO-ORDINATE SYSTEM Â¯XED IN SPACE. THE PROPOSED FORMULATION IS SIMPLE AND THE VALIDATION OF THE MODEL IS SHOWN IN THE EXAMPLE SECTION. FOUR EXAMPLES ARE PRESENTED HERE TO VALIDATE THE FORMULATION.